2015
DOI: 10.5039/agraria.v10i2a5045
|View full text |Cite
|
Sign up to set email alerts
|

Fisiologia e metabolismo foliar em duas variedades de videira sujeitas a um ciclo de défice hídrico e reidratação

Abstract: RESUMOEste trabalho teve como objetivo comparar duas variedades de videira cultivadas em Portugal, Syrah e Touriga Nacional, em termos de suas respostas fisiológicas e bioquímicas a um ciclo de estresse hídrico severo seguido de reidratação. Os tratamentos consistiram em videiras continuamente regadas (FI) e videiras não regadas durante 21 dias e reidratadas após o potencial hídrico foliar de base (Ψ pd ) atingir cerca de -1,1MPa (NI). As observações ocorreram em quatro momentos: i) imediatamente antes de supr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
2
0
1
Order By: Relevance
“…This reduction can be attributed mainly to the lower water absorption by beet plants, thus an alternative to reduce the rate of transpiration is the closure of stomata. However, the closure of stomata also reduces the photosynthetic rate due to the lower availability of CO 2 (Pereira et al, 2013;Ghobadi et al, 2013;Cerqueira et al, 2015), causing the reduction in the growth and development of the plants, corroborating the data obtained in the present work. As for the rate of net photosynthesis, it was observed that there were differences between the two evaluation periods in the evaluated ECw.…”
Section: Resultssupporting
confidence: 90%
“…This reduction can be attributed mainly to the lower water absorption by beet plants, thus an alternative to reduce the rate of transpiration is the closure of stomata. However, the closure of stomata also reduces the photosynthetic rate due to the lower availability of CO 2 (Pereira et al, 2013;Ghobadi et al, 2013;Cerqueira et al, 2015), causing the reduction in the growth and development of the plants, corroborating the data obtained in the present work. As for the rate of net photosynthesis, it was observed that there were differences between the two evaluation periods in the evaluated ECw.…”
Section: Resultssupporting
confidence: 90%
“…In this way, this process may cause the transfer of electrons from the reduced ferredoxin in photosystem I to O 2 , and, consequently, increase the production of ROS, promoting oxidative stress and damage to the plant (Ghobadi et al, 2013;Cerqueira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A baixa concentração de CO 2 na etapa bioquímica da fotossíntese reduz a oxidação de NADPH no ciclo de Calvin-Benson, e, consequentemente, sua disponibilidade sob a forma de NADP + na etapa fotoquímica. Assim, este processo poderá resultar na transferência de elétrons da ferredoxina reduzida no fotossistema I ao O 2, e aumentar a produção de espécies reativas de oxigênio ROS (do inglês Reactive Oxigen Species), com danos ao aparato fotossintético e estresse oxidativo (Pereira et al, 2012;Ghobadi et al, 2013;Cerqueira et al, 2015).…”
Section: Introductionunclassified